Konsep Pembayaran Upah Jasa Pembajak Sawah di Desa Aek Bonban Kecamatan Aek Nabara Barumun Dalam Ekonomi Islam - Afryani Siregar; Junda Harahap; Nur Jannah Nasution (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Based on the results of research conducted that: (1) The concept in Islamic economics is something promised and paid by tenants as compensation or payment for the benefits they enjoy. In principle, anything that can be used as a medium of exchange in buying and selling may be used for payment in wages. In addition, wages must be something of value and permitted by syara' and the amount must be known. The amount of the prescribed wages is known by both parties, both in terms of rent and wages. An appropriate reward according to syara' is something of value and there is pleasure between the two parties. (2) The concept of Islamic economics regarding the payment system for rice field plowing services in Aek Bonban Village, Aek Nabara Barumun District, is in accordance with Islamic economic theory. The land owner gives the plowman's wages at the promised time. For every job of plowing a field, the owner of the field immediately gives his wages. There is a small portion that pays wages later or even after the harvest, but there is no intention to delay or prolong the payment of wages. Even so, this can be understood by both parties, because financially the owner of the rice field must be able to pay wages, and usually. this has been agreed before. because it has fulfilled the pillars and conditions of wages. where in the agreement made between the owner of the rice field and the rice farmer contains the amount of wages and the time of payment of the wages. So that there is no element of fraud in it that can harm either party.